Edukasi Protokol Kesehatan dan Penerapan Program 5M dalam Mencegah Penularan Covid-19 di Pondok Pesantren Hidayatullah - Irsanty Collein; Aminuddin Aminuddin; I Wayan Supetran (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Covid-19 is a pandemic that has spread all over the world. No country is free from the Covid-19 pandemic. Most of the students do not wear masks, do not keep the distance. The number of students who live in Islamic boarding schools is 100 people plus boarding school administrators and school students because in Hidayatullah Islamic boarding school there are also schools that are still open, as well as the surrounding community who carry out worship activities in the mosque area. The purpose of the service was to increase the knowledge of the Hidayatullah Islamic boarding school students and perform a 6-step handwashing simulation. The activity methods are 1) counseling and discussion; 2) Demonstration and distribution of masks and hand sanitizers. Participants were 50 students who were at the Hidayatullah Tondo Islamic Boarding School, conducted at the Mosque. The results showed that there was an increase in students' knowledge about the 5M health protocol, 100% of washing hands. Suggestions for Hidayatullah Islamic Boarding School to further improve supervision related to the use of masks, especially in the classroom and washing hands and make rules for the application of the use of masks by providing sanctions if there are violations. ABSTRAK Covid-19 merupakan pandemi yang berjangkit meluas di seluruh dunia. Tidak ada negara yang bebas dari pandemi Covid-19. Sebagian besar santri tidak menggunakan masker, tidak menjaga jarak. Padahal jumlah santri yang tinggal di pondok pesantren sebanyak 100 orang ditambah dengan pengurus pondok dan siswa sekolah karena di pondok pesantren Hidayatullah juga terdapat sekolah yang tetap dibuka, serta masyarakat sekitar yang melakukan kegiatan ibadah di area masjid. Tujuan pengabdian adalah meningkatkan pengetahuan santri pondok pesantren Hidayatullah serta melakukan simulasi cuci tangan 6 langkah. Metode kegiatan adalah 1) penyuluhan dan diskusi; 2) Demonstrasi dan pembagian masker serta hand sanitizer. Peserta adalah santri yang berada di pondok pesantren Hidayatullah Tondo sebanyak 50 orang, dilakukan di Masjid Pondok. Hasil terdapat peningkatan pengetahuan santri tentang protokol kesehatan 5M, 100% melakukan cuci tangan. Saran bagi Pondok pesantren Hidayatullah untuk lebih meningkatkan kembali pengawasan terkait penggunaan masker terutama di dalam kelas dan cuci tangan serta membuat aturan penerapan penggunaan masker dengan memberikan sanksi apabila ada yang melanggar.